Penggunaan E Logbook Preceptorship untuk Mempermudah Program Preceptorship Perawat Baru di RS X Jakarta: Program Inovasi - Elisabeth Dewi Puspitaningrum; Rr. Tutik Sri Hariyati; Titiek Muhaeriwati; Putri Nilasari (Jurnal Keperawatan Silampari, 2022)
This study aims to improve effective communication between preceptors and preceptees so that the preceptorship program becomes more efficient. The method used is an innovation program for preceptorship activities utilizing a problem-solving approach carried out by four heads of rooms, 22 preceptors, and 12 preceptees. The results of the problem identification obtained that the new nurse orientation management data for the preceptorship method was not optimal, so it needed to be improved through an innovation program that was carried out, namely the E-Logbook Preceptorship. The evaluation results showed that 100% of the participants stated that the use of the E-Logbook Preceptorship was accessible and able to be implemented and helped evaluate the achievements of new nurses. In conclusion, the E-Logbook Preceptorship innovation program started from the assessment and data analysis stage, and the results of the fishbone analysis of the new nurse orientation management were not optimal. The trial results using the E-Logbook Preceptorship are accessible and can be implemented and help evaluate the achievements of new nurses. Keywords: E–Logbook, New Nurse Orientation, Preceptorship